Perancangan Prototype Aplikasi Legalisir Ijazah dan Transkip Akademik Berbasis Web Menggunakan Layanan Autentikasi Single Sign-On Gmail - Arif, Erman (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
The issuance and verification of diplomas is an important process in the world of education. However, this process often encounters obstacles, such as difficulties in collecting and processing data, as well as errors in data input. Therefore, some educational institutions have developed online diploma applications to facilitate the process. This study aims to discuss the development of online diploma applications, their benefits and implications, as well as the challenges and opportunities in the future development of this technology. The research method used is a case study of an educational institution, using a qualitative approach and Agile Development method. In this study, a prototype of an online diploma application has been developed that allows students to access and download their diplomas online and facilitates the diploma verification process by relevant parties. This application is equipped with a good data security and privacy system to ensure user data security. In conclusion, online diploma applications have the potential to improve the efficiency and effectiveness of the diploma issuance and verification process. However, the development of this application also requires serious attention to data security and privacy aspects.